Capitalising on the crowd: the monetary and financial ecologies of crowdfunding - Langley, Paul; Leyshon, Andrew (SAGE, 2016)
‘Crowdfunding’ is a method of raising money and finance to capitalise projects of various kinds. Drawing on the networking capabilities of the internet and software platforms, those seeking project funding appeal to potentially diverse audiences who are collectively referred to as ‘the crowd’. What practitioners, advocates and policymakers typically identify within crowdfunding is its ‘alternative’, ‘disruptive’ and ‘democratising’ qualities; that is, it is held to be a novel, digitally-rendered economic space which has the capacity to challenge established funding practices in banking, capital markets and venture capital networks, offering a more open and egalitarian source of capital for economic, social and cultural entrepreneurship. The paper develops the concept of ‘ecologies’, drawn from the geographies of money and finance literature, to advance a critical understanding of the crowdfunding economy that is sceptical of its apparent qualities. First, the concept of ecologies encourages the analysis of diverse and proliferative monetary and financial forms, enabling an understanding that avoids the binary opposition of ‘capitalist/alternative’ economic forms and which differentiates between the variegated crowdfunding ecologies that have emerged to date. Second, by foregrounding the intermediation processes and credit-debt relations of monetary and financial ecologies, it is argued that crowdfunding may largely replicate rather than disrupt the extant institutional and debt dynamics of funding practices. Third, by emphasizing the socio-spatial effects of monetary and financial ecologies, attention is drawn to the need for further research into the unevenness that mitigates against crowdfunding being as open and egalitarian as its advocates claim.